Atividade citotóxica do óleo essencial das folhas de Myrcia splendens em células tumorais - Montalvão, Monalisa Martins (2022)
Cancer is the second most fatal disease in the world, followed only to cardiovascular diseases and becoming a serious public health problem. The main form of treatment for cancer patients is chemotherapy, with the use of anticancer drugs. However, despite being effective, conventional antineoplastics causes adverse effects in patients, since they do not have selectivity for tumor cells. In this context, given the limitations of conventional chemotherapy treatments, cancer patients all over the world have looking for complementary therapies, such as the use of natural products derived from plants. The objective of this work was to carry out the chemistry characterization and evaluate the in vitro antitumor effect of the essential oil from the leaves of the species Myrcia splendens (OEMS), in different tumor lines. For this, the hydrodistillation of the leaves and the analysis of the OEMS by GC-MS were performed, and identified the bicyclogermacrene, the e-caryophyllene and the germacrene D, all sesquiterpenes, as major constituents. The in vitro cytotoxicity of OEMS was evaluated in three tumor cell lines: lung adenocarcinoma (A549), melanoma (B16-F10) and acute monocytic leukemia (THP-1), using the MTT assay. OEMS showed cytotoxicity in all strains tested, with IC50 ranging between 5.37 and 20.14 µg / mL. In view of this result, the A549 lung cancer strain was used, due to the high incidence and mortality rates of this cancer, to continue the trials to evaluate the antitumor activity of the OEMS. The ability of OEMS to inhibit the formation of clones of the A549 cell line was evaluated by clonogenic assay. The results available show that OEMS was able to significantly inhibit the formation of clones at all concentrations tested (10, 20 and 40 µg / mL). In addition, in assay with DAPI and Phalloidin / FITC, used to verify morphological changes in cells, it was possible to observe that OEMS induced cell death by apoptosis in A549 cells in the tested concentrations (10, 20 and 40 µg / mL), evidenced by the characteristics of reduced cytoplasmic volume and DNA fragmentation. Furthermore, cell shrinkage was observed at the concentration of 40 µg / mL of the OEMS. OEMS was also able to reduce the migratory capacity of A549 cells at a concentration of 40 µg/mL. Given the results, it is suggested that OEMS has antitumor activity in vitro, showing promise for future cancer treatments.